The critical role of direct observation in entrustment decisions - Matthew Sibbald (Canadian Medical Education Journal, 2021)
Background: Entrustment decisions may be retrospective (based on past experiences with a trainee) or real-time (based on direct observation). We investigated judgments of entrustment based on assessor prior knowledge of candidates and based on systematic direct observation, conducted in an objective structured clinical exam (OSCE).